De novo EIF2AK1 and EIF2AK2 Variants Are Associated with Developmental Delay, Leukoencephalopathy, and Neurologic Decompensation. - Mao, Dongxue; Reuter, Chloe M; Ruzhnikov, Maura R Z; Beck, Anita E; Farrow, Emily G; Emrick, Lisa T; Rosenfeld, Jill A; Mackenzie, Katherine M; Robak, Laurie; Wheeler, Matthew T; Burrage, Lindsay C; Jain, Mahim; et al. (Am J Hum Genet, 2020)
EIF2AK1 and EIF2AK2 encode members of the eukaryotic translation initiation factor 2 alpha kinase (EIF2AK) family that inhibits protein synthesis in response to physiologic stress conditions. EIF2AK2 is also involved in innate immune response and the regulation of signal transduction, apoptosis, cell proliferation, and differentiation. Despite these findings, human disorders associated with deleterious variants in EIF2AK1 and EIF2AK2 have not been reported. Here, we describe the identification of nine unrelated individuals with heterozygous de novo missense variants in EIF2AK1 (1/9) or EIF2AK2 (8/9). Features seen in these nine individuals include white matter alterations (9/9), developmental delay (9/9), impaired language (9/9), cognitive impairment (8/9), ataxia (6/9), dysarthria in probands with verbal ability (6/9), hypotonia (7/9), hypertonia (6/9), and involuntary movements (3/9). Individuals with EIF2AK2 variants also exhibit neurological regression in the setting of febrile illness or infection. We use mammalian cell lines and proband-derived fibroblasts to further confirm the pathogenicity of variants in these genes and found reduced kinase activity. EIF2AKs phosphorylate eukaryotic translation initiation factor 2 subunit 1 (EIF2S1, also known as EIF2α), which then inhibits EIF2B activity. Deleterious variants in genes encoding EIF2B proteins cause childhood ataxia with central nervous system hypomyelination/vanishing white matter (CACH/VWM), a leukodystrophy characterized by neurologic regression in the setting of febrile illness and other stressors. Our findings indicate that EIF2AK2 missense variants cause a neurodevelopmental syndrome that may share phenotypic and pathogenic mechanisms with CACH/VWM.
Keywords: Adolescent; Ataxia; Child; Child, Preschool; Developmental Disabilities; eIF-2 Kinase; Female; Genetic Variation; Hereditary Central Nervous System Demyelinating Diseases; Humans; Infant; Leukoencephalopathies; Male; Nervous System Malformations; White Matter

Dominant-negative mutations in human IL6ST underlie hyper-IgE syndrome. - Béziat, Vivien; Tavernier, Simon J; Chen, Yin-Huai; Ma, Cindy S; Materna, Marie; Laurence, Arian; Staal, Jens; Aschenbrenner, Dominik; Roels, Lisa; Worley, Lisa; Claes, Kathleen; Gartner, Lisa; et al. (J Exp Med, 2020)
Autosomal dominant hyper-IgE syndrome (AD-HIES) is typically caused by dominant-negative (DN) STAT3 mutations. Patients suffer from cold staphylococcal lesions and mucocutaneous candidiasis, severe allergy, and skeletal abnormalities. We report 12 patients from 8 unrelated kindreds with AD-HIES due to DN IL6ST mutations. We identified seven different truncating mutations, one of which was recurrent. The mutant alleles encode GP130 receptors bearing the transmembrane domain but lacking both the recycling motif and all four STAT3-recruiting tyrosine residues. Upon overexpression, the mutant proteins accumulate at the cell surface and are loss of function and DN for cellular responses to IL-6, IL-11, LIF, and OSM. Moreover, the patients' heterozygous leukocytes and fibroblasts respond poorly to IL-6 and IL-11. Consistently, patients with STAT3 and IL6ST mutations display infectious and allergic manifestations of IL-6R deficiency, and some of the skeletal abnormalities of IL-11R deficiency. DN STAT3 and IL6ST mutations thus appear to underlie clinical phenocopies through impairment of the IL-6 and IL-11 response pathways.
Keywords: Adolescent; Alleles; C-Reactive Protein; Cell Membrane; Cells, Cultured; Child; Cytokine Receptor gp130; Cytokines; Female; Fibroblasts; Genes, Dominant; Genetics, Population; HEK293 Cells; Humans; Job Syndrome; Kinetics; Loss of Function Mutation; Male; Middle Aged; Models, Biological; Mutation; Pedigree; Phenotype; Th2 Cells; Up-Regulation; Young Adult

Missed diagnoses: Clinically relevant lessons learned through medical mysteries solved by the Undiagnosed Diseases Network. - Cope, Heidi; Spillmann, Rebecca; Rosenfeld, Jill A; Brokamp, Elly; Signer, Rebecca; Schoch, Kelly; Kelley, Emily G; Sullivan, Jennifer A; Macnamara, Ellen; Lincoln, Sharyn; Golden-Grant, Katie; Orengo, James P; et al. (Mol Genet Genomic Med, 2020)
BACKGROUND: Resources within the Undiagnosed Diseases Network (UDN), such as genome sequencing (GS) and model organisms aid in diagnosis and identification of new disease genes, but are currently difficult to access by clinical providers. While these resources do contribute to diagnoses in many cases, they are not always necessary to reach diagnostic resolution. The UDN experience has been that participants can also receive diagnoses through the thoughtful and customized application of approaches and resources that are readily available in clinical settings. METHODS: The UDN Genetic Counseling and Testing Working Group collected case vignettes that illustrated how clinically available methods resulted in diagnoses. The case vignettes were classified into three themes; phenotypic considerations, selection of genetic testing, and evaluating exome/GS variants and data. RESULTS: We present 12 participants that illustrate how clinical practices such as phenotype-driven genomic investigations, consideration of variable expressivity, selecting the relevant tissue of interest for testing, utilizing updated testing platforms, and recognition of alternate transcript nomenclature resulted in diagnoses. CONCLUSION: These examples demonstrate that when a diagnosis is elusive, an iterative patient-specific approach utilizing assessment options available to clinical providers may solve a portion of cases. However, this does require increased provider time commitment, a particular challenge in the current practice of genomics.
Keywords: Adolescent; Child; Child, Preschool; Databases, Factual; Diagnosis, Computer-Assisted; Female; Genetic Diseases, Inborn; Genetic Testing; Humans; Information Dissemination; Male; Middle Aged; Missed Diagnosis; National Institutes of Health (U.S.); Phenotype; Precision Medicine; Undiagnosed Diseases; United States; Young Adult

De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
BACKGROUND: Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 encodes a transcriptional co-regulator structurally related to RAI1, the dosage-sensitive gene responsible for Smith-Magenis syndrome (deletion/haploinsufficiency) and Potocki-Lupski syndrome (duplication/triplosensitivity). METHODS: Genome-wide analyses by exome sequencing (ES) and chromosomal microarray analysis (CMA) identified individuals with heterozygous, likely damaging, loss-of-function alleles in TCF20. We implemented further molecular and clinical analyses to determine the inheritance of the pathogenic variant alleles and studied the spectrum of phenotypes. RESULTS: We report 25 unique inactivating single nucleotide variants/indels (1 missense, 1 canonical splice-site variant, 18 frameshift, and 5 nonsense) and 4 deletions of TCF20. The pathogenic variants were detected in 32 patients and 4 affected parents from 31 unrelated families. Among cases with available parental samples, the variants were de novo in 20 instances and inherited from 4 symptomatic parents in 5, including in one set of monozygotic twins. Two pathogenic loss-of-function variants were recurrent in unrelated families. Patients presented with a phenotype characterized by developmental delay, intellectual disability, hypotonia, variable dysmorphic features, movement disorders, and sleep disturbances. CONCLUSIONS: TCF20 pathogenic variants are associated with a novel syndrome manifesting clinical characteristics similar to those observed in Smith-Magenis syndrome. Together with previously described cases, the clinical entity of TCF20-associated neurodevelopmental disorders (TAND) emerges from a genotype-driven perspective.
Keywords: Adolescent; Child; Child, Preschool; Craniofacial Abnormalities; Developmental Disabilities; Female; Humans; INDEL Mutation; Infant; Intellectual Disability; Male; Muscle Hypotonia; Smith-Magenis Syndrome; Transcription Factors; Young Adult

Corner fracture type spondylometaphyseal dysplasia: Overlap with type II collagenopathies. - Machol, Keren; Jain, Mahim; Almannai, Mohammed; Orand, Thibault; Lu, James T; Tran, Alyssa; Chen, Yuqing; Schlesinger, Alan; Gibbs, Richard; Bonafe, Luisa; Campos-Xavier, Ana Belinda; Unger, Sheila; et al. (Am J Med Genet A, 2017)
Spondylometaphyseal dysplasia (SMD) corner fracture type (also known as SMD "Sutcliffe" type, MIM 184255) is a rare skeletal dysplasia that presents with mild to moderate short stature, developmental coxa vara, mild platyspondyly, corner fracture-like lesions, and metaphyseal abnormalities with sparing of the epiphyses. The molecular basis for this disorder has yet to be clarified. We describe two patients with SMD corner fracture type and heterozygous pathogenic variants in COL2A1. These two cases together with a third case of SMD corner fracture type with a heterozygous COL2A1 pathogenic variant previously described suggest that this disorder overlaps with type II collagenopathies. The finding of one of the pathogenic variants in a previously reported case of spondyloepimetaphyseal dysplasia (SEMD) Strudwick type and the significant clinical similarity suggest an overlap between SMD corner fracture and SEMD Strudwick types. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Amino Acid Substitution; Bone Diseases, Developmental; Child, Preschool; Collagen Type II; Diagnosis, Differential; Exome; Genetic Association Studies; Genotype; Growth Disorders; High-Throughput Nucleotide Sequencing; Hip Joint; Humans; Infant; Male; Mutation; Osteochondrodysplasias; Phenotype; Radiography; Tibial Fractures

Heterozygous variants in ACTL6A, encoding a component of the BAF complex, are associated with intellectual disability. - Marom, Ronit; Jain, Mahim; Burrage, Lindsay C; Song, I-Wen; Graham, Brett H; Brown, Chester W; Stevens, Servi J C; Stegmann, Alexander P A; Gunter, Andrew T; Kaplan, Julie D; Gavrilova, Ralitza H; Shinawi, Marwan; et al. (Hum Mutat, 2017)
Pathogenic variants in genes encoding components of the BRG1-associated factor (BAF) chromatin remodeling complex have been associated with intellectual disability syndromes. We identified heterozygous, novel variants in ACTL6A, a gene encoding a component of the BAF complex, in three subjects with varying degrees of intellectual disability. Two subjects have missense variants affecting highly conserved amino acid residues within the actin-like domain. Missense mutations in the homologous region in yeast actin were previously reported to be dominant lethal and were associated with impaired binding of the human ACTL6A to β-actin and BRG1. A third subject has a splicing variant that creates an in-frame deletion. Our findings suggest that the variants identified in our subjects may have a deleterious effect on the function of the protein by disturbing the integrity of the BAF complex. Thus, ACTL6A gene mutation analysis should be considered in patients with intellectual disability, learning disabilities, or developmental language disorder.
Keywords: Actins; Adolescent; Child; Chromatin Assembly and Disassembly; Chromosomal Proteins, Non-Histone; DNA Helicases; DNA-Binding Proteins; Exome; Face; Female; Hand Deformities, Congenital; Heterozygote; Humans; Intellectual Disability; Male; Micrognathism; Multiprotein Complexes; Mutation, Missense; Nuclear Proteins; Protein Binding; Transcription Factors

Neonatal fractures as a presenting feature of LMOD3-associated congenital myopathy. - Abbott, Megan; Jain, Mahim; Pferdehirt, Rachel; Chen, Yuqing; Tran, Alyssa; Duz, Mehmet B; Seven, Mehmet; Gibbs, Richard A; Muzny, Donna; Lee, Brendan; Marom, Ronit; Burrage, Lindsay C (Am J Med Genet A, 2017)
Nemaline myopathy is a rare inherited disorder characterized by weakness, hypotonia, and depressed deep tendon reflexes. It is clinically and genetically heterogeneous, with the most severe phenotype presenting as perinatal akinesia, severe muscle weakness, feeding difficulties and respiratory failure, leading to early mortality. Pathogenic variants in 12 genes, encoding components of the sarcomere or factors related to myogenesis, have been reported in patients affected with the disorder. Here, we describe an early, lethal presentation of decreased fetal movements, hypotonia, muscle weakness, and neonatal respiratory failure requiring ventilator support in three siblings from a consanguineous family. All exhibited perinatal fractures, and thus, a skeletal dysplasia was considered as possibly contributing to the phenotype. However, whole exome sequencing revealed a homozygous, loss-of-function pathogenic variant in LMOD3, which has recently been associated with nemaline myopathy and, in a subset of patients, perinatal fractures. This case demonstrates the importance of considering congenital neuromuscular disorders in the differential diagnosis of perinatal fractures.
Keywords: Female; Fractures, Bone; Homozygote; Humans; Infant, Newborn; Male; Muscle Proteins; Mutation; Myopathies, Structural, Congenital; Pedigree

Use of Exome Sequencing for Infants in Intensive Care Units: Ascertainment of Severe Single-Gene Disorders and Effect on Medical Management. - Meng, Linyan; Pammi, Mohan; Saronwala, Anirudh; Magoulas, Pilar; Ghazi, Andrew Ray; Vetrini, Francesco; Zhang, Jing; He, Weimin; Dharmadhikari, Avinash V; Qu, Chunjing; Ward, Patricia; Braxton, Alicia; et al. (JAMA Pediatr, 2017)
Importance: While congenital malformations and genetic diseases are a leading cause of early infant death, to our knowledge, the contribution of single-gene disorders in this group is undetermined. Objective: To determine the diagnostic yield and use of clinical exome sequencing in critically ill infants. Design, Setting, and Participants: Clinical exome sequencing was performed for 278 unrelated infants within the first 100 days of life who were admitted to Texas Children's Hospital in Houston, Texas, during a 5-year period between December 2011 and January 2017. Exome sequencing types included proband exome, trio exome, and critical trio exome, a rapid genomic assay for seriously ill infants. Main Outcomes and Measures: Indications for testing, diagnostic yield of clinical exome sequencing, turnaround time, molecular findings, patient age at diagnosis, and effect on medical management among a group of critically ill infants who were suspected to have genetic disorders. Results: The mean (SEM) age for infants participating in the study was 28.5 (1.7) days; of these, the mean (SEM) age was 29.0 (2.2) days for infants undergoing proband exome sequencing, 31.5 (3.9) days for trio exome, and 22.7 (3.9) days for critical trio exome. Clinical indications for exome sequencing included a range of medical concerns. Overall, a molecular diagnosis was achieved in 102 infants (36.7%) by clinical exome sequencing, with relatively low yield for cardiovascular abnormalities. The diagnosis affected medical management for 53 infants (52.0%) and had a substantial effect on informed redirection of care, initiation of new subspecialist care, medication/dietary modifications, and furthering life-saving procedures in select patients. Critical trio exome sequencing revealed a molecular diagnosis in 32 of 63 infants (50.8%) at a mean (SEM) of 33.1 (5.6) days of life with a mean (SEM) turnaround time of 13.0 (0.4) days. Clinical care was altered by the diagnosis in 23 of 32 patients (71.9%). The diagnostic yield, patient age at diagnosis, and medical effect in the group that underwent critical trio exome sequencing were significantly different compared with the group who underwent regular exome testing. For deceased infants (n = 81), genetic disorders were molecularly diagnosed in 39 (48.1%) by exome sequencing, with implications for recurrence risk counseling. Conclusions and Relevance: Exome sequencing is a powerful tool for the diagnostic evaluation of critically ill infants with suspected monogenic disorders in the neonatal and pediatric intensive care units and its use has a notable effect on clinical decision making.
Keywords: Adult; Critical Care; Disease Management; Exome; Genetic Counseling; Genetic Diseases, Inborn; Humans; Infant; Infant Care; Infant, Newborn; Intensive Care Units, Pediatric; Length of Stay; Retrospective Studies; Texas; Whole Exome Sequencing

MIPEP recessive variants cause a syndrome of left ventricular non-compaction, hypotonia, and infantile death. - Eldomery, Mohammad K; Akdemir, Zeynep C; Vögtle, F-Nora; Charng, Wu-Lin; Mulica, Patrycja; Rosenfeld, Jill A; Gambin, Tomasz; Gu, Shen; Burrage, Lindsay C; Al Shamsi, Aisha; Penney, Samantha; Jhangiani, Shalini N; et al. (Genome Med, 2016)
BACKGROUND: Mitochondrial presequence proteases perform fundamental functions as they process about 70 % of all mitochondrial preproteins that are encoded in the nucleus and imported posttranslationally. The mitochondrial intermediate presequence protease MIP/Oct1, which carries out precursor processing, has not yet been established to have a role in human disease. METHODS: Whole exome sequencing was performed on four unrelated probands with left ventricular non-compaction (LVNC), developmental delay (DD), seizures, and severe hypotonia. Proposed pathogenic variants were confirmed by Sanger sequencing or array comparative genomic hybridization. Functional analysis of the identified MIP variants was performed using the model organism Saccharomyces cerevisiae as the protein and its functions are highly conserved from yeast to human. RESULTS: Biallelic single nucleotide variants (SNVs) or copy number variants (CNVs) in MIPEP, which encodes MIP, were present in all four probands, three of whom had infantile/childhood death. Two patients had compound heterozygous SNVs (p.L582R/p.L71Q and p.E602*/p.L306F) and one patient from a consanguineous family had a homozygous SNV (p.K343E). The fourth patient, identified through the GeneMatcher tool, a part of the Matchmaker Exchange Project, was found to have inherited a paternal SNV (p.H512D) and a maternal CNV (1.4-Mb deletion of 13q12.12) that includes MIPEP. All amino acids affected in the patients' missense variants are highly conserved from yeast to human and therefore S. cerevisiae was employed for functional analysis (for p.L71Q, p.L306F, and p.K343E). The mutations p.L339F (human p.L306F) and p.K376E (human p.K343E) resulted in a severe decrease of Oct1 protease activity and accumulation of non-processed Oct1 substrates and consequently impaired viability under respiratory growth conditions. The p.L83Q (human p.L71Q) failed to localize to the mitochondria. CONCLUSIONS: Our findings reveal for the first time the role of the mitochondrial intermediate peptidase in human disease. Loss of MIP function results in a syndrome which consists of LVNC, DD, seizures, hypotonia, and cataracts. Our approach highlights the power of data exchange and the importance of an interrelationship between clinical and research efforts for disease gene discovery.
Keywords: Adult; Amino Acid Sequence; Female; Genes, Recessive; Heart Defects, Congenital; Humans; Infant; Infant, Newborn; Male; Metalloendopeptidases; Muscle Hypotonia; Pedigree; Phenotype; Sequence Homology, Amino Acid; Sudden Infant Death; Syndrome

Autosomal-Dominant Multiple Pterygium Syndrome Is Caused by Mutations in MYH3. - Chong, Jessica X; Burrage, Lindsay C; Beck, Anita E; Marvin, Colby T; McMillin, Margaret J; Shively, Kathryn M; Harrell, Tanya M; Buckingham, Kati J; Bacino, Carlos A; Jain, Mahim; Alanay, Yasemin; Berry, Susan A; et al. (Am J Hum Genet, 2015)
Multiple pterygium syndrome (MPS) is a phenotypically and genetically heterogeneous group of rare Mendelian conditions characterized by multiple pterygia, scoliosis, and congenital contractures of the limbs. MPS typically segregates as an autosomal-recessive disorder, but rare instances of autosomal-dominant transmission have been reported. Whereas several mutations causing recessive MPS have been identified, the genetic basis of dominant MPS remains unknown. We identified four families affected by dominantly transmitted MPS characterized by pterygia, camptodactyly of the hands, vertebral fusions, and scoliosis. Exome sequencing identified predicted protein-altering mutations in embryonic myosin heavy chain (MYH3) in three families. MYH3 mutations underlie distal arthrogryposis types 1, 2A, and 2B, but all mutations reported to date occur in the head and neck domains. In contrast, two of the mutations found to cause MPS in this study occurred in the tail domain. The phenotypic overlap among persons with MPS, coupled with physical findings distinct from other conditions caused by mutations in MYH3, suggests that the developmental mechanism underlying MPS differs from that of other conditions and/or that certain functions of embryonic myosin might be perturbed by disruption of specific residues and/or domains. Moreover, the vertebral fusions in persons with MPS, coupled with evidence of MYH3 expression in bone, suggest that embryonic myosin plays a role in skeletal development.
Keywords: Arthrogryposis; Cytoskeletal Proteins; Exome; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Mutation; Myosins; Osteogenesis

De Novo GMNN Mutations Cause Autosomal-Dominant Primordial Dwarfism Associated with Meier-Gorlin Syndrome. - Burrage, Lindsay C; Charng, Wu-Lin; Eldomery, Mohammad K; Willer, Jason R; Davis, Erica E; Lugtenberg, Dorien; Zhu, Wenmiao; Leduc, Magalie S; Akdemir, Zeynep C; Azamian, Mahshid; Zapata, Gladys; Hernandez, Patricia P; et al. (Am J Hum Genet, 2015)
Meier-Gorlin syndrome (MGS) is a genetically heterogeneous primordial dwarfism syndrome known to be caused by biallelic loss-of-function mutations in one of five genes encoding pre-replication complex proteins: ORC1, ORC4, ORC6, CDT1, and CDC6. Mutations in these genes cause disruption of the origin of DNA replication initiation. To date, only an autosomal-recessive inheritance pattern has been described in individuals with this disorder, with a molecular etiology established in about three-fourths of cases. Here, we report three subjects with MGS and de novo heterozygous mutations in the 5' end of GMNN, encoding the DNA replication inhibitor geminin. We identified two truncating mutations in exon 2 (the 1(st) coding exon), c.16A>T (p.Lys6(∗)) and c.35_38delTCAA (p.Ile12Lysfs(∗)4), and one missense mutation, c.50A>G (p.Lys17Arg), affecting the second-to-last nucleotide of exon 2 and possibly RNA splicing. Geminin is present during the S, G2, and M phases of the cell cycle and is degraded during the metaphase-anaphase transition by the anaphase-promoting complex (APC), which recognizes the destruction box sequence near the 5' end of the geminin protein. All three GMNN mutations identified alter sites 5' to residue Met28 of the protein, which is located within the destruction box. We present data supporting a gain-of-function mechanism, in which the GMNN mutations result in proteins lacking the destruction box and hence increased protein stability and prolonged inhibition of replication leading to autosomal-dominant MGS.
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Cell Cycle; Child, Preschool; Congenital Microtia; Dwarfism; Exons; Female; Geminin; Gene Expression; Genes, Dominant; Growth Disorders; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Micrognathism; Molecular Sequence Data; Mutation; Patella; Pedigree; Protein Stability; Proteolysis; RNA Splicing; Sequence Alignment

The genetic basis of DOORS syndrome: an exome-sequencing study. - Campeau, Philippe M; Kasperaviciute, Dalia; Lu, James T; Burrage, Lindsay C; Kim, Choel; Hori, Mutsuki; Powell, Berkley R; Stewart, Fiona; Félix, Têmis Maria; van den Ende, Jenneke; Wisniewska, Marzena; Kayserili, Hülya; et al. (Lancet Neurol, 2014)
BACKGROUND: Deafness, onychodystrophy, osteodystrophy, mental retardation, and seizures (DOORS) syndrome is a rare autosomal recessive disorder of unknown cause. We aimed to identify the genetic basis of this syndrome by sequencing most coding exons in affected individuals. METHODS: Through a search of available case studies and communication with collaborators, we identified families that included at least one individual with at least three of the five main features of the DOORS syndrome: deafness, onychodystrophy, osteodystrophy, intellectual disability, and seizures. Participants were recruited from 26 centres in 17 countries. Families described in this study were enrolled between Dec 1, 2010, and March 1, 2013. Collaborating physicians enrolling participants obtained clinical information and DNA samples from the affected child and both parents if possible. We did whole-exome sequencing in affected individuals as they were enrolled, until we identified a candidate gene, and Sanger sequencing to confirm mutations. We did expression studies in human fibroblasts from one individual by real-time PCR and western blot analysis, and in mouse tissues by immunohistochemistry and real-time PCR. FINDINGS: 26 families were included in the study. We did exome sequencing in the first 17 enrolled families; we screened for TBC1D24 by Sanger sequencing in subsequent families. We identified TBC1D24 mutations in 11 individuals from nine families (by exome sequencing in seven families, and Sanger sequencing in two families). 18 families had individuals with all five main features of DOORS syndrome, and TBC1D24 mutations were identified in half of these families. The seizure types in individuals with TBC1D24 mutations included generalised tonic-clonic, complex partial, focal clonic, and infantile spasms. Of the 18 individuals with DOORS syndrome from 17 families without TBC1D24 mutations, eight did not have seizures and three did not have deafness. In expression studies, some mutations abrogated TBC1D24 mRNA stability. We also detected Tbc1d24 expression in mouse phalangeal chondrocytes and calvaria, which suggests a role of TBC1D24 in skeletogenesis. INTERPRETATION: Our findings suggest that mutations in TBC1D24 seem to be an important cause of DOORS syndrome and can cause diverse phenotypes. Thus, individuals with DOORS syndrome without deafness and seizures but with the other features should still be screened for TBC1D24 mutations. More information is needed to understand the cellular roles of TBC1D24 and identify the genes responsible for DOORS phenotypes in individuals who do not have a mutation in TBC1D24. FUNDING: US National Institutes of Health, the CIHR (Canada), the NIHR (UK), the Wellcome Trust, the Henry Smith Charity, and Action Medical Research.
Keywords: Adolescent; Carrier Proteins; Child; Child, Preschool; Craniofacial Abnormalities; Exome; Female; Hand Deformities, Congenital; Hearing Loss, Sensorineural; Humans; Infant; Intellectual Disability; Internationality; Male; Nails, Malformed; Phenotype; Sequence Analysis, DNA; Young Adult

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors